Eosinophilic Esophagitis in Children: Clinical Cases - A. V. Burlutskaya; A. V. Statova; O. V. Dolbneva; I. I. Borlakova; J. V. Pisotskaya; D. V. Ustyuzhanina (Кубанский научный медицинский вестник, 2022)
Background. Eosinophilic esophagitis (Ee) is a chronic immune-mediated disease of the esophagus, which is characterized by symptoms of esophageal dysfunction and marked eosinophilic infiltration of the mucous membrane (MM) of the organ. Currently, interest in the problem of eosinophilic esophagitis in the global medical scientific community is steadily growing. Eosinophilic esophagitis has no pathognomonic symptoms, which causes a great difficulty for diagnosis.Clinical case description. The paper describes two clinical cases of eosinophilic esophagitis in patient T. (4 years 10 months) and patient M. (5 years 2 months). Patient T. was admitted to the gastroenterology department of the Children’s Regional Clinical Hospital (CRCH), with complaints of hiccups, flatulence, intermittent abdominal pain, coughing when swallowing. The medical history showed that the child has been ill since the beginning of March 2021, when pain appeared in the epigastric region and along the esophagus when eating. Parents sought help in the Central District Hispital, where surgical and ENT pathologies were excluded. The child was referred to the gastroenterological department of the CRCH, where, according to the results of esophagogastroduodenoscopy (EGDS), the diagnosis of “Erosive reflux — esophagitis” was made. After stopping the erosive process the patient underwent repeated EGDS with biopsy, and was diagnosed with “Eosinophilic esophagitis”. Prescribed treatment: hypoallergenic diet, topical glucocorticosteroids (fluticasone propionate), proton pump inhibitors (PPIs), antacids. As a result of the treatment, no improvement was noted — it was decided to transfer the patient to budesonide therapy in the form of a viscous suspension, after which a persistent positive effect was observed. In the second case, the girl M. was admitted to the gastroenterological department of the Children’s Clinical Hospital with complaints of constant nausea after eating and abdominal pain. The medical history showed that the child has been sick since she was 1. The examination also revealed moderate eosinophilia, an increase in the level of alkaline phosphatase. Fibrogastroduodenoscopy with biopsy revealed endoscopic signs of EoE. A diagnosis of eosinophilic esophagitis was made. Treatment: hypoallergenic diet, glucocorticosteroids, PPI, antacids, antiemetic drugs. The treatment brought about certain positive dynamics. Conclusion. The presented clinical cases show the difficulty of diagnosing eosinophilic esophagitis, since the symptoms of this disease are not very specific.